Making paper aeroplanes (Journal of Parents and Teachers, 2026)
Primary school pupils develop scientific research skills through flying and making paper aeroplanes. This hands-on approach enables pupils to take an active role in their own learning by linking theory with practice.
Keywords: Methodology; Active; Scientific Research; Learning; Experimentation